2019
DOI: 10.1038/s41467-019-10868-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in primary auditory cortex represent sound source location in a cue-invariant manner

Abstract: Auditory cortex is required for sound localisation, but how neural firing in auditory cortex underlies our perception of sound sources in space remains unclear. Specifically, whether neurons in auditory cortex represent spatial cues or an integrated representation of auditory space across cues is not known. Here, we measured the spatial receptive fields of neurons in primary auditory cortex (A1) while ferrets performed a relative localisation task. Manipulating the availability of binaural and spectral localis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The shift by 2.3˚ was calculated as the difference between the across-subjects mean PSE values in postVA-and postAV-adaptation phases from the psychometric functions. While accumulating research has shown that sound location is coded by broadly tuned neural populations in auditory cortices in mammals (Werner-Reiss and Groh, 2008;Wood et al, 2019), less is known about auditory spatial coding in parietal or frontal cortices from single cell neurophysiology. For instance, one previous neurophysiology study in non-human primates has suggested that neurons in parietal area VIP have narrow auditory receptive fields that are congruent with visual receptive fields (Schlack et al, 2005).…”
Section: Spatial Hemifield Modelmentioning
confidence: 99%
“…The shift by 2.3˚ was calculated as the difference between the across-subjects mean PSE values in postVA-and postAV-adaptation phases from the psychometric functions. While accumulating research has shown that sound location is coded by broadly tuned neural populations in auditory cortices in mammals (Werner-Reiss and Groh, 2008;Wood et al, 2019), less is known about auditory spatial coding in parietal or frontal cortices from single cell neurophysiology. For instance, one previous neurophysiology study in non-human primates has suggested that neurons in parietal area VIP have narrow auditory receptive fields that are congruent with visual receptive fields (Schlack et al, 2005).…”
Section: Spatial Hemifield Modelmentioning
confidence: 99%
“…We applied SIT to study sound localization in freely behaving and engaged animals. Traditionally used paradigms to study spatial sensitivity require a constant head position during sound presentation (Wood et al, 2019), often in naïve or anesthetized animals (Middlebrooks and Knudsen, 1984). In contrast, aSIT loc allows investigations in the locomoting animal during active localization, providing more naturalistic conditions and, thus, higher ecological relevance.…”
Section: Sound Localization (Asit Loc )mentioning
confidence: 99%
“…The auditory cortex has been viewed as the ultimate step in processing the rich acoustic stream constantly reaching our ears and also as a key structure in cognitive tasks involving auditory stimuli ( Weinberger and Diamond, 1987 ; Edeline, 1999 ; Weinberger, 2004 ; Ohl and Scheich, 2005 ; Fritz et al, 2007 ). Indeed, the plasticity of auditory cortex network has been described in many situations ranging from frequency discrimination ( Edeline and Weinberger, 1993 ; Edeline et al, 1993 ; Fritz et al, 2003 , 2005 ) or spatial discrimination tasks ( Lee and Middlebrooks, 2011 ; Wood et al, 2019 ) to pitch extraction ( Bizley et al, 2013 ), attentional tasks ( Otazu et al, 2009 ), selective attention ( Wittekindt et al, 2014 ), and predictive coding ( Malmierca et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%